Urban transformation in Istanbul and Budapest: Neoliberal governmentality in the EU's semi-periphery and its limits. (May 2015) - Akçalı, Emel; Korkut, Umut
Abstract: By discussing the variety and variability of urban neoliberal governmentality and its limits in the semi-periphery of the advanced capitalist world, the article aims to explore the embeddedness of neoliberalism at the dawn of the new millennium. Cities that are increasingly becoming parts of the global economy, despite being on the periphery of advanced capitalism, host a myriad of diverse forms of neoliberal governmentality in terms of spatial change. Although responding with enthusiasm to the increasing mobility of capital and the internationalization of investments through gentrification plans, the current transformative efforts of Istanbul and Budapest under two conservative governments indicate, for instance, the re-invention of authoritarianism so that these cities serve the purposes of their national leaders. This development signals a hybrid form of governmentality that combines neoliberalism with illiberal logics and manifests similar processes in different locations despite disparities in scale, local needs and characteristics. The article further argues that since such urban transformations take place within the neo-conservative leaders' battles to acquire cultural and social capital, they create potential to make both metropolises the new rebel cities of Europe, albeit with divergent levels of resistance.